2018
DOI: 10.1038/s41598-018-19446-3
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the Zanclean megaflood in the eastern Mediterranean Basin

Abstract: The Messinian salinity crisis (MSC) - the most abrupt, global-scale environmental change since the end of the Cretaceous – is widely associated with partial desiccation of the Mediterranean Sea. A major open question is the way normal marine conditions were abruptly restored at the end of the MSC. Here we use geological and geophysical data to identify an extensive, buried and chaotic sedimentary body deposited in the western Ionian Basin after the massive Messinian salts and before the Plio-Quaternary open-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(111 citation statements)
references
References 34 publications
3
106
0
2
Order By: Relevance
“…As a result, the basin is defined as cylindrical, parallel to the advancing orogenic wedge. In consideration of the high base level of the Mediterranean Sea, restored after Messinian Salinity Crisis (Micallef et al, 2018), and the presence of deep-water deposits only next to the main thrusts, we infer an underfill phase of the PPAF during early Pliocene time (profile A-A' relative to PL1 and PL2 stages in Figure 11). At the intra-Piacenzian PL3 stage, the NA tectonic activity evolved with non-self-parallel arcuate thrust-folds, located in the central part of the foredeep basin (profiles A-A' relative to the PL3 map in Figure 11).…”
Section: Plio-pleistocene Evolution Of the Ppafmentioning
confidence: 97%
See 1 more Smart Citation
“…As a result, the basin is defined as cylindrical, parallel to the advancing orogenic wedge. In consideration of the high base level of the Mediterranean Sea, restored after Messinian Salinity Crisis (Micallef et al, 2018), and the presence of deep-water deposits only next to the main thrusts, we infer an underfill phase of the PPAF during early Pliocene time (profile A-A' relative to PL1 and PL2 stages in Figure 11). At the intra-Piacenzian PL3 stage, the NA tectonic activity evolved with non-self-parallel arcuate thrust-folds, located in the central part of the foredeep basin (profiles A-A' relative to the PL3 map in Figure 11).…”
Section: Plio-pleistocene Evolution Of the Ppafmentioning
confidence: 97%
“…In this sector, the delta complex evolved after an erosive phase responsible for the foreland exposure during late Messinian sea-level drop (Amadori, Garcia-Castellanos, et al, 2018). PL1u with erosive features (V-shaped canyons in Figure 6b) lies at the base of the sequence, evolved during the post-Messinian Salinity Crisis mega-flooding phase (Micallef et al, 2018) and supplied by the eastern Southern Alps.…”
Section: Base Pliocene Pl1 Phase (Figures 7a and 9a)mentioning
confidence: 99%
“…Uplift near the present-day strait of Gibraltar restricted the Atlantic-Mediterranean marine gateways in the latest Miocene, resulting in an overall negative hydrological budget in the basins of the Mediterranean Sea (Gorini, Montadert, & Rabineau, 2015;Lofi et al, 2011;Roveri, Flecker et al, 2014a;Ryan, 2008Ryan, , 2011. This facilitated one of the most dramatic episodes of oceanic transition of the past 20 million years, maybe even since the Cretaceous; the MSC (Feng et al, 2016;Hsü, 1974;Krijgsman, Hilgen, Raffi, Sierro, & Wilson, 1999;Micallef et al, 2018;Netzeband et al, 2006;Pérez-Asensio, Aguirre, Jiménez-Moreno, Schmiedl, & Civis, 2013). During this catastrophic event, the Mediterranean basins experienced cyclic hypersaline conditions and deposition of a thick evaporite series.…”
Section: Geologic Settingmentioning
confidence: 99%
“…However, İşler et al (2005), Aksu et al (2009Aksu et al ( , 2018, Hall et al (2005Hall et al ( , 2009Hall et al ( , 2014, Castellanos et al (2009), Güneş et al (2018a, 2018c, and Lymer et al (2018aLymer et al ( , 2018b have shown mainly three prominent seismic stratigraphic units: Pliocene-Quaternary (unit 1), Messinian (unit 2), and Pre-Messinian (unit 3), identified by using seismic reflection and well data in the area. Micallef (2018) identified the units as Plio-Quaternary fine-grained marine sediments (unit 1) and Messinian evaporites (unit 3), which are locally separated by a distinct body with chaotic to transparent seismic characteristics (Lofi et al, 2011a(Lofi et al, , 2011bRoveri et al, 2014aRoveri et al, , 2014bCameselle and Urgeles, 2017;Aksu et al, 2018;Lymer et al, 2018aLymer et al, , 2018bGüneş et al, 2018aGüneş et al, , 2018bGüneş et al, , 2018c. According to Dunbar and Rodgers (1957), unconformities are surfaces of erosion and/or nondeposition that constitute time-gaps in the geological record.…”
Section: Seismic Description and Interpretationmentioning
confidence: 99%